2013
DOI: 10.1590/1414-431x20132809
|View full text |Cite
|
Sign up to set email alerts
|

ChIP-seq analysis of histone H3K9 trimethylation in peripheral blood mononuclear cells of membranous nephropathy patients

Abstract: Membranous nephropathy (MN), characterized by the presence of diffuse thickening of the glomerular basement membrane and subepithelial in situ immune complex disposition, is the most common cause of idiopathic nephrotic syndrome in adults, with an incidence of 5-10 per million per year. A number of studies have confirmed the relevance of several experimental insights to the pathogenesis of human MN, but the specific biomarkers of MN have not been fully elucidated. As a result, our knowledge of the alterations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…The variants in this gene are associated with developmental delays and mental retardation and may be relevant to autism-related spectrum disorders [ 30 32 ]. Disruption of CNTN4 is also thought to cause cognitive defects [ 33 ]. Our study showed strong association of SUA concentrations with CNTN4 SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…The variants in this gene are associated with developmental delays and mental retardation and may be relevant to autism-related spectrum disorders [ 30 32 ]. Disruption of CNTN4 is also thought to cause cognitive defects [ 33 ]. Our study showed strong association of SUA concentrations with CNTN4 SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of computational analyses and experimental validation revealed that a high proportion of unmapped ChIP-Seq reads were mappable after being subjected to a taxonomic classification and subsequent remapping using SHRiMP, a short read aligner capable of mapping reads to highly polymorphic regions of the genome. We discovered that these previously ignored reads, also reported in ChIP-Seq experiments conducted with various modified histones 27 28 29 30 harbor key information that showed novel aspects important for the reconstruction of gene regulatory grids. By focusing on the human TAL1 TF, a set of previously unaligned reads were shown to have mappable properties and have been used for identification and validation of novel TAL1 binding sites, revealing important characteristics on how this TF can regulate cell fate determination, apoptosis, and potential novel role in sensory perception.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, studying epigenetic features, such as DNA methylation, may offer new insights by providing a mechanism to understand how each individual’s genome interacts with their environment through the epigenome. However, this review highlights that only a small number of studies have been reported researching differential methylation in rare renal diseases: IgAN [4850]ADPKD [5153]Rare diseases causing proteinuria including membranous nephropathy [54, 55] and focal segmental glomerulosclerosis (FSGS) [5659]Congenital renal agenesis [60]…”
Section: Discussionmentioning
confidence: 99%
“…Rare diseases causing proteinuria including membranous nephropathy [54, 55] and focal segmental glomerulosclerosis (FSGS) [5659]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation